Enhancing potential of SME Financing through Blockchain Smart Lending - Alla IVASHCHENKO1; Yevheniia POLISHCHUK1; Serhii SMERICHEVSKYI1; Liubov POPOVA2 (Communications of International Proceedings, 2020)
The research is aimed to analyze the simplifying ways of getting access to finance by SMEs through such FinTech tool as Blockchain smart lending. The main focus of the paper is to give insight on potential benefits and probable risks of being involved into Blockchain lending as for potential borrowers, namely SMEs, as well as for lenders. The new trend of P2P lending via Blockchain was explored in details and cross-lending platform analysis was conducted regarding identification its potential strengths and weaknesses. Authors revealed that some Blockchain platforms could be controlled by financial or governmental institutions which could be considered as the approach for eliminating risk of mistrusting and probable fraud. Such innovation tools in relation to ensure digital assets, as stablecoins, CDP accounts and MKR tokens were observed. In spite of decentralization nature of Blockchain, it is relevant to establish due diligence procedure and some governmental control because of behavioristic component in relations between lenders, borrowers and platform administrators in order to eradicate possible cases of scam activity.
Keywords: SME; Blockchain; Smart lending; P2P platform